PERAN OPERATOR EMIS PADA KANTOR KEMENTERIAN AGAMA KABUPATEN SOLOK - Arnal Yanuardi; Marzalisman Marzalisman; Elpi Sumarni (Jurnal Public Administration, Business and Rural Develoment Planning, 2023)
The purpose of this study is to analyze the role of the operator. Research using descriptive qualitative method. The information in this study was that there were three people consisting of PAI emis operators, Madrasah EMIS operators and Islamic boarding school operators. Data collection techniques using interviews and observation. The results of the study show the importance of realizing data management in organizing data, including data collection, data processing, data maintenance and output/results (reporting) of data in the Ministry of Religion of Solok Regency effectively by utilizing information technology in the EMIS management system. There is a simplification in the process and activities of organizing and organizing data owned by the Ministry of Religion of Solok Regency. While the supporting factor is the adequate level of competence of human resources so that there is ease in obtaining data/information because if information is needed by the operator related to EMIS needs, it will be immediately announced through several media, namely through the WhatsApp application. The inhibiting factor for technical problems is the willingness of the internet network. Based on the results of the research above, it can be concluded that the important role of the EMIS operator for the Ministry of Solok Regency can minimize obstacles in managing Emis data which is supported by the availability of a high internet / Wifi network. Besides that, EMIS operators continue to improve competence by participating in training activities, technical guidance and so on